PENERAPAN METODE DISCOVERY UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI TARI DI KELAS VII. 10 SMP NEGERI 18 PADANG - Suci Ardilawaty; Zora Iriani; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2018)
Abstract This Article aims to explain and describe the improvement of student learning outcomes by using Discovery Method in the learning of dance arts at the SMP Negeri 18 Padang in Padang. The type of research was classroom action research carried out in two cycles. The research subjects were 7th-grade students of SMP Negeri 18 Padang with a total was 31 people. Data collection instruments used was observation sheets, field notes, and knowledge (Cognitive) and skills (Psychomotor) test results. The results of this study indicate that learning using Discovery Method succeeded in improving the learning outcomes of 7th-grade students of SMP Negeri 18 Padang. It is proved by the improvement of student learning outcomes in cycle I and cycle II where there is a very good improvement. In the first cycle, the result of the skills test (psychomotor) was 60%. As well as the first cycle test results for tests of knowledge (cognitive) for test learning outcomes was 54%. Cycle II learning test results on the skills test (psychomotor) are 93.54%. As well as the second cycle test for knowledge (cognitive) is 96.77%. Thus the use of Discovery Method to improve learning outcomes in dance art learning in 7th-grade students of SMP Negeri 18 Padang has been well achieved. Keywords: The Application, Discovery Method, The Results Of The Study, The Art Of Dance